Participatory Design Approach in Architectural Education, a Field Survey About User Saticfaction - Bulut, Halise Betul; Polatoglu, Cigdem (SCIENCEPARK SCI, ORGANIZATION & COUNSELING LTD, 2017)
This study aims to emphasize the importance of participatory design approach in architectural education via user satisfaction through recently applied public project.The field study is conducted in 2013, and Kucukcekmece Urban Square Project is chosen to examine the users meanings and the responds of the designs. Observation and interview were used in the study. Following the search, it's seen that majority is not satisfied with the new organization. Users compared the new one with the old square and said that the new square could be better.ln conjunction with architectural design education, participatory design approach should be involved to the studio. With participatory design in education, students will learn to respect rights and thought of users and so, there will be satisfied users and this situation will contribute to provide social sustainability.
Keywords: architectural education; participatory design; user satisfaction; Education & Educational Research